2010
DOI: 10.1002/cphc.200900938
|View full text |Cite
|
Sign up to set email alerts
|

Supramolecular Organization and Chiral Resolution of p‐Terphenyl‐m‐Dicarbonitrile on the Ag(111) Surface

Abstract: The supramolecular organization and layer formation of the non-linear, prochiral molecule [1, 1';4',1'']-terphenyl-3,3"-dicarbonitrile adsorbed on the Ag(111) surface is investigated by scanning tunneling microscopy (STM) and near-edge X-ray absorption fine-structure spectroscopy (NEXAFS). Upon two-dimensional confinement the molecules are deconvoluted in three stereoisomers, that is, two mirror-symmetric trans- and one cis-species. STM measurements reveal large and regular islands following room temperature d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
57
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 37 publications
(68 citation statements)
references
References 62 publications
11
57
0
Order By: Relevance
“…Furthermore, the antiparallel alignment of the polar groups results in the relative displacement of one covalent chain against the other along the main chain direction such that the butadiyne sections of one wire (marked blue) are lining up with the terphenyl sections of the second wire (marked red). Similar binding motifs have been observed before for a related carbonitrile‐terphenyl species or in the double‐strand formation with carboxylic acid units A recent theoretical analysis quantified that each CN group contributes with a binding energy of around 0.1 eV. Accordingly, oligomeric double chain segments should exhibit a significant temperature stability due to accumulated interchain bonding.…”
supporting
confidence: 74%
“…Furthermore, the antiparallel alignment of the polar groups results in the relative displacement of one covalent chain against the other along the main chain direction such that the butadiyne sections of one wire (marked blue) are lining up with the terphenyl sections of the second wire (marked red). Similar binding motifs have been observed before for a related carbonitrile‐terphenyl species or in the double‐strand formation with carboxylic acid units A recent theoretical analysis quantified that each CN group contributes with a binding energy of around 0.1 eV. Accordingly, oligomeric double chain segments should exhibit a significant temperature stability due to accumulated interchain bonding.…”
supporting
confidence: 74%
“…In contrast, the bent, nonlinear linkers are prochiral and thus can display a multiplicity of distinct network elements due to the symmetry‐breaking effect of the surface. Using a nonlinear linker featuring an increased conformational phase space due to the positioning of the CN moieties at meta positions ( m NC‐Ph 3 ‐ m CN) ( Figure a) the supramolecular organization and layer formation of the prochiral molecule absorbed on the Ag(111) surface was investigated 36…”
Section: Supramolecular Engineeringmentioning
confidence: 99%
“…c) High‐resolution STM images of a densely packed highly ordered molecular island on the Ag(111) substrate composed of L ‐ trans molecules (top) and D ‐ trans molecules (bottom). Adapted with permission 36…”
Section: Supramolecular Engineeringmentioning
confidence: 99%
“…As an as-deposited sample warmed up, molecules were dissociated from the edges of chevron islands. It has been reported that such edge dissociation can occur at about 300 K, including molecular systems that have stronger intermolecular bonds (about 1 eV per molecule) than DBAQ bonds, and that well-ordered molecular structures coexist with a disordered 2D liquid phase of molecules [33][34][35]. Likewise, DBAQ molecules may have a 2D liquid phase at 300 K that coexists with chevron structures.…”
Section: Resultsmentioning
confidence: 99%